Calibration of nuclear recoils at the 100 eV scale using neutron capture. (19th July 2021) - Thulliez, L.; Lhuillier, D.; Cappella, F.; Casali, N.; Cerulli, R.; Chalil, A.; Chebboubi, A.; Dumonteil, E.; Erhart, A.; Giuliani, A.; Gunsing, F.; Jericha, E.; et al.
Abstract: The development of low-threshold detectors for the study of coherent elastic neutrino-nucleus scattering and for the search for light dark matter necessitates methods of low-energy calibration. We suggest this can be provided by the nuclear recoils resulting from the γ emission following thermal neutron capture. In particular, several MeV-scale single-γ transitions induce well-defined nuclear recoil peaks in the 100 eV range. Using the FIFRELIN code, complete schemes of γ-cascades for various isotopes can be predicted with high accuracy to determine the continuous background of nuclear recoils below the calibration peaks. We present a comprehensive experimental concept for the calibration of CaWO4 and Ge cryogenic detectors at a research reactor. For CaWO4 the simulations show that two nuclear recoil peaks at 112.5 eV and 160.3 eV should be visible above background simply in the spectrum of the cryogenic detector. Then we discuss how the additional tagging for the associated γ increases the sensitivity of the method and extends its application to a wider energy range and to Ge cryogenic detectors.